A modification of He's variational approach using the least square method to nonlinear oscillators. Issue 3 (December 2019) - Arif, Muhammad Shoaib; Nawaz, Yasir; Bibi, Mairaj; Fayyaz, Rabia; Naz, Mehvish
In this paper, we apply the global error minimization method to nonlinear oscillators with fractional terms for determining the first- and second-order approximate frequencies and solutions. The estimation problem is transformed into a minimization problem which leads to a simple yet precise scheme for finding the frequency of oscillation and the solution of the ordinary differential equation.